PARADIGMA PENDIDIKAN DESAIN DI INDONESIA - Iswahyudi Iswahyudi (Jurnal Cakrawala Pendidikan, 2003)
The design activity in Indonesia has done for years ago, equal with development ofthis nation. Even traditional design education was educated before prehistory periods, then through to palaces periods in this Archipelago by personal activity in the villages or in workshop that palaces need. The institution of modem design education begin at Dutch Government, because based on "ethical politics" to support the society to get their development. After Indonesia got their freedom, especially institution oftop design education has to be growth and are path in all college that have fine arts subject. Especially for ITB that considered as pioneer to yield modem design product because have succeed to transform Bauhaus Curricuhim as center ofworld modem design institution. Because Indonesia became a industrial country, the consequently is some ofmaterials to fulfil ~esign is increase, and its spreader to all ofmy region with the product and can be makes vacancy. Based on the symptom was found paradigm ofdesign education, and stay up anticipation ofdesign and to path product ofIndonesia design in international society. Key words: Institution ofTraditional Design Education, Modern, Bauhaus Paradigm